Peranan Delapan Keterampilan Dasar Mengajar Dalam Meningkatkan Kemampuan Mengajar Mahasiswa - Abdul, Arief Rachman Hakim; Irawan, Safri; Haryani, Meri; Haryanto, Arief; Prasetyo, Agung; Nurkhoiroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of basic teaching skills in improving the teaching ability of Sports Coaching Education (PKO) students at Gorontalo State University (UNG). Basic teaching skills, consisting of eight main skills, are considered important to prepare prospective teachers to face challenges in the field. This study used a one-group pre-test post-test design with a sample of 22 students who attended the Micro Teaching course. Data were collected through observation of teaching skills in the pre-test and post-test, which were then analyzed using a t-test to determine whether there was an increase in teaching ability after the treatment. The results showed that there was a significant increase in students' teaching ability, as reflected in the significant difference between the pre-test and post-test results (p < 0.05). Thus, it can be concluded that the application of basic teaching skills has a positive effect on improving the teaching ability of PKO UNG students, which in turn can affect the quality of teaching in schools